Analisis Pencatatan Akuntansi Pembiayaan Rahn (Gadai) di BMT. UGT. Sidogiri Capem. Banyuputih Situbondo Berdasarkan PSAK 107 - Sukandi, Sukandi; Shoimah, Imroatus; Sa’diyah, Halimatus (Program Studi Akuntansi Syari'ah Universitas Ibrahimy, 2023)
Each Islamic financial institution may have a different strategy and operational system in order to increase the interest of its target consumers. It can be in the form of providing convenience to financing customers in terms of administrative requirements, but still carrying out strict selection and supervision to anticipate the risk of default (default). As is the case with BMT. UGT. Sidogiri in implementing rahn or mortgage financing. Another aspect is in terms of accounting records of transactions carried out by the company. Then, how is the accounting treatment applied in BMT. UGT. Sidogiri Capem. Banyuputih towards rahn financing. This qualitative descriptive research was carried out at the BMT sub-branch office. UGT. Sidogiri which is located in the Banyuputih sub-district, Situbondo. Data sources consist of primary and secondary data, which are collected through observation, interviews and documentation. As well as testing the validity of the data with triangulation. The conclusions obtained by the researcher are: that in terms of recognition, measurement, and presentation of rahn financing it is in accordance with PSAK 107. Meanwhile in terms of disclosure it is still not in accordance with PSAK 107.